HUBUNGAN ANTARA LAYANAN BIMBINGAN DAN KONSELING DENGAN KESULITAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA MADRASAH TSANAWIYAH NEGERI I MOJOKERTO - Miftakhul Djanah; Imam Mustai’n; Abdul Rouf; Dian Triana (FAI- Undar, 2019)
This study aims to identify the effect of guidance and counseling services on student learning difficulties in Madrasah Tsanawiyah Negeri I Mojokerto.The hypothesis proposed is